SISTEM MONITORING EFEKTIVITAS KINERJA PANEL SURYA DENGAN PENAMBAHAN REFLEKTOR BERBASIS MIKROKONTROLER - Tania Astari Trisnandini; Nurhedhi Desryanto; ismail kgs (Website, 2022)
Utilization of Solar Panels as a fulfillment of electrical energy needs is very important, considering the conventional power sources currently used are very limited, which does not rule out the possibility of scarcity in the future. For this reason, a solar panel development was made with the addition of a flat mirror reflector in order to increase the effectiveness of performance. besides the implementation of the development of microcontroller technology as a monitoring system, so that the data obtained can be done automatically, continuously and stored. In this design, it uses current and voltage sensor which will be processed by the microcontroller with data results in the form of current, voltage and power values ​​as well as time information for the resulting data. The data that shows the effectiveness of the performance of solar panels in this study is to compare the power generated by solar panels between solar panels without reflectors, solar panels with additional reflectors with installation angles of 450 and 750, so that it is known that the greatest efficiency value is in the performance of solar panels with additional reflectors installation angle of 750 is 1.06%.